PERAN PERILAKU PEMIMPIN DAN KOMITMEN GURU DALAM MENINGKATKAN PRESTASI KERJA GURU (STUDI KASUS PADA SD N 67/IV DESA TANJUNG GEDANG) - Duwi Puspa Ningsih; Hendriyaldi Hendriyaldi; Feny Tialonawarmi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
research aims to analyze the role of leadership behavior and teacher commitment in improving teacher work performance. The subjects of this research are the principal, teachers, and staff at SD N 67/VI Tanjung Gedang. The study employs a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research population consists of the principal and all teaching staff, totaling 12 individuals. The findings reveal two main points: (1) the principal’s leadership behavior plays a crucial role in encouraging and enhancing teacher performance, and (2) teacher commitment significantly contributes to improving the quality and outcomes of their work. Thus, leadership behavior and teacher commitment are proven to play an important role in enhancing teacher work performance